What Factors Affect the Intention of Using Islamic Mobile Apps? An Analysis Using the UTAUT-2 Model - Ivan Alviyana; Lina Setiawati (Politeknik Negeri Bandung, 2023)
The use of Islamic applications in the current digital era has grown rapidly since users can access anything and everything with just a few clicks. The market potential of M-Productivity applications in Indonesia is large since this country possesses the largest Muslim population in the world with more than 200 million Islam believers. However, this chance seems to be neglected by application developers in Indonesia. This study attempts to investigate the factors that influence consumer intentions to use Islamic M-Productivity applications by employing the UTAUT 2 model as the research model. A self-administered questionnaire was distributed, and 320 valid responses were generated from Muslim users who have or are currently using Islamic M-Productivity applications. PLS-SEM was applied as a data analysis technique to examine the hypotheses of this study. The results explain that performance expectancy and habit significantly influence a person's intention to access Islamic M-Productivity applications. In addition, this study theoretically enriches the literature on consumer intentions to use Islamic mobile applications and their factors.